Painful hypoadrenalism. (28th March 2011) - Hoshino, Chisho; Satoh, Noriyuki; Narita, Masashi; Kikuchi, Akio; Inoue, Minoru
Abstract : A 61-year-old man presented with diffuse myalgia and arthralgia. The physical examination showed diffuse musculoskeletal tenderness and joint stiffness without the presence of synovitis or arthritis. Nerve conduction study showed combined mild axonal degenerative and demyelinating change. Muscle biopsy analysis showed unspecific mild muscle atrophy with myopathic changes found on electromyography. A diagnosis of isolated adrenocorticotropic hormone deficiency was made on the basis of endocrinological evaluation. The widespread musculoskeletal pain resolved as a result of administration of physiological dose of hydrocortisone replacement. In a patient with unexplained rheumatic symptoms, adrenocortical insufficiency should be considered in the possible aetiology.